Economic and Legal Mechanisms of Interstate Support for Agricultural Producers - Bazenov, Airat B.; Begzhan, Aizat M.; Zhunissov, Zhassulan S.; Tazhikov, Abzal K.; Amandossuly, Bagdat (International Journal of Criminology and Sociology, 2022)
The transitional stage in the agrarian economy requires an optimal combination of state protection and market levers. At present, the state regulatory influence on the development of agriculture remains, on the one hand, quite significant, and on the other, insufficiently effective. There is no systemic integrity in the practice of state regulation of the agricultural sector. The relevance of the study is that in transition economies, agrarian protectionism was initially caused by somewhat different circumstances, and the protectionist policy was formed in fundamentally different conditions. The authors demonstrate that protectionism in industrial-type transition economies inherited a huge mechanism of state support for the agro-industrial complex in the depths of a centrally planned economy. Everywhere this support constituted a heavy burden of national finances, and one of the primary tasks of reforms in transition economies, including agrarian reforms, was precisely the release from this burden. It causes sharp liberalization of agrarian policy in almost all countries. The method of analysis was used to investigate the main directions, methods, and mechanisms of state regulation of the economy in different countries; the priority areas of state regulation of prices in the agro-industrial complex industry were highlighted. The practical significance of the study is that macroeconomic reforms in countries with an industrial type of development led to a rapid deterioration in the financial situation of the agricultural sector.